Narrative Analysis of Jataka Stories at Muara Jambi Temple Tourist Attrac-tion: Systematic Literature Review - Damana, I Ketut (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
The purpose of this study was to identify, evaluate, and synthesize relevant literature to reveal the relationship between the Jataka stories and archaeological remains in the area and their implications for the development of culture-based tourism. The method used in this study is a Systematic Literature Review with a qualitative approach. Limitations include the lack of direct field verification to evaluate the extent to which local cultural practices are currently influenced by Buddhist values. The data collection process was carried out through identification of scientific literature from academic databases, screening based on inclusion and exclusion criteria, and thematic analysis of Jataka narratives and symbols relevant to Muara Jambi Temple. The results of the study indicate that a number of narrative elements in the Jataka stories are reflected in the reliefs, structures, and artifacts at Muara Jambi Temple, indicating the important role of Buddhist moral teachings in shaping the cultural identity of the site. This study also found that the use of Jataka story narratives as part of cultural tourism interpretation can increase the appeal and educational value of Muara Jambi Temple. These findings are expected to be the basis for a more meaningful strategy for preserving and developing cultural heritage-based tourism